Assessment of variability among inbreds, hybrids and populations of sun flower (Helianthus annuus) - RANGANATHA, A R G; ANJANA, R M; NAGARAJ, G (The Indian Journal of Agricultural Sciences, 2011)
Sunflower is the source of highly nutritious edible oil with very good levels of linoleic acid, the essential fatty acid. Variation in the fatty acid profile of’ inbreds, hybrids and populations has been studied. In general, the sunflower oil of Indian cultivars had around 40-65% linoleic acid. The ’DRSF- 108’ population and the ’PCSH-243’, new hybrid had 42% oleic and 50% linoleic acid, a balanced specbum of fatty acids. While some inbreds Iiad around 65-70% linoleic acid, however other lines had 50-55% oleic acid. In general, high variability for fatty acids among the inbreds, hybrids and populations has been observed in the present material.